Analisis Tentang Penilaian Kinerja Keuangan Dengan Menggunakan Metode Economic Value Added (EVA) Pada Koperasi Bakthi SMPN 3 Watansoppeng - Irnayani; Masyadi (Jurnal Bisnis Digital dan Enterpreneur (BISENTER), 2023)
Financial performance is a result or achievement achieved in a certain period. In this study, the assessment of financial performance was carried out using the EVA (Economic Value Added) method where this method was considered better than the ratio analysis. This study aims to evaluate the financial performance of the Bakthi Cooperative of SMPN 3 Watansoppeng. By using the EVA (Economic Value Added) method analysis tool during the 2018 research year is the same as 2020. This research is quantitative and qualitative research with data collection techniques in the form of interviews and documentation in the form of annual financial statements. Furthermore, it is analyzed using the EVA (Economic Value Added) method. From the results of research using the EVA method, it can be seen that the EVA value at the Bakthi Cooperative of SMPN 3 Watansoppeng experienced a negative value in 2018 which means that there is no value increase and the cooperative's financial performance is not good. In 2019-2020 the EVA value > 0 or positive value. The positive EVA shows that cooperatives are able to provide economic added value and good financial performance. This study also used multiple linear regression analysis techniques that were processed using SPSS software. Based on the results of the analysis, it shows that EVA has no effect on NOPAT, Cost of Capital, WACC and Invested Capital.